Penerapan Kode Etik Perusahaan Melalui Whistle Blower Dalam Meningkatkan Kinerja Perusahaan. (Studi Kasus Pada Pt. Sreeya Sewu Indonesia, Tbk) - Evita Vibriana Wulandari; R.A. Kadarmanta; Muslim (CV. ITTC INDONESIA, 2024)
A business organization or Company is established to develop its business in accordance with the Company's vision and mission in the future for the sustainability of the Company. In addition, the purpose of the business is to make a profit. The benefits it gets are for the welfare of its employees. Factually in the lives of both developed and developing societies, cases of crime and deviations from the rules often occur, so efforts are needed to prevent them. The Corporate Code of Ethics is a internal guidelines that apply are binding within the Company. The Code of Business Ethics reflects the actions and values we hold in interacting with all stakeholders, employees, customers, governments, partners and communities to build long-term relationships with them. Whistleblowing in various public institutions has played a role in exposing various cases of fraud and violations as well as the environment of companies or offices of private companies, similar cases 35% (Nations on Occupational Fraud and Abuse, 2021). The research is to produce a concept based on a scientific approach about the importance of improving company performance through the application of the Company's code of ethics through whistleblowing and encouraging employees to have concern and courage as well as honesty in reporting violations of laws and ethics that they are aware of to internal authorities either directly or indirectly through appointed third parties so that immediate action can be taken to solve the problem.